SULFUR-MODIFIED MELAMINE-FORMALDEHYDE COATED UREA IN SALINE-SODIC SOIL: ENHANCING SOIL NITROGEN USE EFFICIENCY AND UREASE INHIBITION (Journal of Medical & Health Sciences Review, 2025)
This study investigates the synthesis of melamine-formaldehyde-based aminoplast resin incorporated with sodium metabisulfite as a sulfur compound to create a polymer-composite coating for urea granules. The coated urea granules were applied in saline-sodic soil to inhibit urease activity and improve radish plant productivity. Coating levels of 5%, 4%, 3%, 2%, and 1% sodium metabisulfite in melamine-formaldehyde resin enhanced productivity in terms of shoot and fruit biomass. The synthesis achieved a 95% product yield, and FT-IR analysis confirmed successful cross-linking and sulfur integration in the polymer composite. This research highlights the potential of sulfur-enriched melamine-formaldehyde composites to improve nitrogen fertilizer efficiency and plant productivity under challenging soil conditions. The phytochemicals profile of the radish plant was also investigated after the treatment and it has been found that improved nutrient profile was explored.